Alkoholatkorrosion von Aluminium (EN AC‐48100), Einfluss von Temperatur sowie Ethanol‐ und Wassergehalt. Issue 6 (20th June 2013) - Tuchscheerer, F.; Krüger, L.; Mandel, M.; Müller, S.; Liebsch, S.
<x xml:space="preserve">Abstract</x> The corrosion behaviour of the aluminium alloy EN AC‐48100 (Al‐17wt%Si‐4wt%Cu‐Mg) was investigated in ethanol fuels with different contents of water (0.05 vol.‐%, 0.2 vol.‐%, 0.35 vol.‐%), at different temperatures (20°C, 60°C, 80°C), and with different contents of ethanol (10 vol.‐%, 25 vol.‐%, 50 vol.‐%, 85 vol.‐%). A interdependency of the corrosion with the temperature and the water content in the fuels was determined. At a temperature of 80°C in an ethanol fuel with less than 0.05 vol.‐% water, strong corrosion starts soon after immersion. An influence of the ethanol content to the degree of corrosion was determined for fuels with ethanol contents below 25 vol.‐% notably. Based on the observations and measurements, a theory for the multi stage character of the corrosion mechanism of aluminium alloys in dry ethanol fuels was developed.